Is wine savory? Umami taste in wine - António, Inês (2016)
Umami is an important taste element in natural products like wine. The umami taste has distinctive properties that differentiate it from other tastes, including a taste-enhancing synergism between two umami compounds, L-glutamate and 5’-ribonulceotides, and a prolonged aftertaste. In human taste cells, taste buds transduce the chemicals that elicit the umami tastes into membrane depolarization, which triggers release of transmitter to activate gustatory afferent nerve fibers. Umami taste stimuli are primarily received by type II receptor cells which contain the T1R and T2R families of G protein-coupled taste receptors. The taste sensation of umami requires protein hydrolysis which renders free glutamic acid. The main components of the nitrogen fraction of musts and wines are amino acids, peptides, proteins and ammonium ion. Their presence in wine is from amino acids of grapes, enzymatic degradation of grape proteins, excretion by living yeasts at the end of fermentation and to proteolysis during yeast autolysis. Thus, amino acids are important contributors of the wine savory taste and flavor.